2017
DOI: 10.1080/09537104.2017.1371290
|View full text |Cite
|
Sign up to set email alerts
|

Screening for platelet function disorders with Multiplate and platelet function analyzer

Abstract: Light transmission aggregation (LTA) is the gold standard for the diagnosis of platelet function disorders (PFDs), but it is time-consuming and limited to specialized laboratories. Whole-blood impedance aggregometry (Multiplate) and platelet function analyzer (PFA) may be used as rapid screening tools to exclude PFDs. The aim of this study is to assess the diagnostic performance of Multiplate and PFA for PFDs, as detected by LTA.Data from preoperative patients, patients referred to the hematologist for bleedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 30 publications
7
55
0
Order By: Relevance
“…It was not until later that physicians started to incorporate the BAT into their standard anamnesis. However, this tool might not be as usable in screening for other haemostatic disorders as previously thought . Another disadvantage of BAT scores is that these scores increase in time and are not based on time intervals.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It was not until later that physicians started to incorporate the BAT into their standard anamnesis. However, this tool might not be as usable in screening for other haemostatic disorders as previously thought . Another disadvantage of BAT scores is that these scores increase in time and are not based on time intervals.…”
Section: Discussionsupporting
confidence: 88%
“…In previous studies, measuring PFA was found to be an insensitive screenings assay, especially for patients with mild PFD’s . It was considered not very useful since the PFA cannot differentiate between different PFD’s and vWD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…5,8,24 The agonist concentrations used for MEA in the present study are, therefore, lower than concentrations used in previous studies of normal controls or patients. 15,[19][20][21]25 The threshold concentrations for ADP, collagen, and TRAP used in the present study are similar to those identified by Toth et al, 13 although the anticoagulant used for the present study was different (sodium heparin rather than citrate or hirudin). Reference intervals were developed for these agonist concentrations using healthy control subjects, with cutoff values determined as two SDs below the mean.…”
Section: Measupporting
confidence: 82%
“…The value of the PFA was assessed as it is often used to screen for platelet function disorders (PFDs), 28 even though previous studies demonstrated low sensitivity for mild PFDs. 29,30 The aPTT is quite often prolonged due to the presence of lupus anticoagulant activity, which can lead to an extensive but unnecessary coagulation work-up. 31 Our findings underpin the advice of the ESA 5 and the SFAR 6 guidelines that in case of a positive bleeding history, hematologist consultation is preferred over measurement of PT or aPTT.…”
Section: Discussionmentioning
confidence: 99%